Influence choreographic readiness to gymnasts final assessment of performance skills - Omelichyk-Ziurkalova, O.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to provide a quantitative assessment and expert choreographic preparedness gymnasts. Material : the study involved eight gymnasts competition finalists in the floor exercise - female members of the Ukrainian national team in gymnastics. Results : the quantitative indicators of acrobatic and dance elements to determine the baseline assessment. Defined methods complications composition on the floor exercise by reducing the number of acrobatic lines and diagonals and increase the number of gymnastic elements. The theoretical performance of the composite sequence is improved structure and increases the difficulty of the exercise. Conclusions : in the process of composition complications need to pay more attention to the technique of performing gymnastic elements. In improving exercise choreography element replace (in some cases) acrobatic element. Based on the results is planned future direction of research in order to improve the training process in gymnastics.